Design and Construction of Ultraviolet and Incoming Solar Irradiance Sensing Device - Osinowo M. Olatunde; Willoughby A. Alexander; Dairo O. Feyisayo; Ewetumo Theophilus; Kolawole L. Babatope (Iraqi Journal of Science, 2022)
In-situ measurements of ultraviolet (UV) and solar irradiance is very sparse in Nigeria because of cost; it is estimated using meteorological parameters. In this work, a low-cost UV and pyranometer device, using locally sourced materials, was developed. The instrument consists of a UV sensor (ML8511), a photodiode (BPW34) housed in a carefully sealed vacuumed glass bulb, the UV and solar irradiance sensor amplifiers, a 16-bit analog-to-digital converter (ADS1115), Arduino mega 2560, liquid crystal display (LCD) and microSD card for data logging. The designed amplifier has an offset voltage of 0.8676 mV. The sensitivity of the irradiance device is 86.819 Wm-2/mV with a correcting factor of 27.77 Wm-2 and a maximum range of 1200 Wm-2. The instrument validation error is 9.67% and a correlation coefficient of 0.89 when compared with a standard SRS100 pyranometer. The UV sensor showed a close response with a correlation of 0.99 in comparison with a standard Skye instrument. From 08:00 to 16:00 local time (LT), there is a very close agreement between the standard device and the developed counterpart, with marginal differences of about 9.6% observed at the two extremes.